Pengaruh Audit Tenure, Kompleksitas Operasi, Opini Audit Dan Ukuran Kantor Akuntan Publik (KAP) Terhadap Audit Delay - Hilal Al Ambia; Afrizal; Riski Hernando (LPPM UBP, 2022)
This study aims to provide empirical evidence of the effect of audit tenure, operation complexity, audit opinion and size of public accounting firm (KAP) on audit delay simultaneously and partially. The population in this study are building construction sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling technique used is purposive sampling. The sample used in this study were 16 companies for 4 years with a total of 64 observational data. The data analysis technique used is descriptive statistics and multiple linear regression analysis. The results of this study indicate that audit tenure, operation complexity, audit opinion, and the size of a public accounting firm (KAP) simultaneously affect on audit delay. Operation complexity and audit opinion partially affect on audit delay. Audit tenure and the size of the public accounting firm (KAP) partially have no effect on audit delay.